Ghrelin and Obestatin Levels in Rheumatoid Arthritis - Koca, Suleyman Serdar; Ozgen, Metin; Aydin, Suleyman; Dag, Sait; Evren, Bahri; Isik, Ahmet (Springer/Plenum Publishers, 2008)
Background: Ghrelin is a powerful, endogenous orexigenic peptide. In addition, ghrelin has anti-inflammatory effects, and it has been reported that ghrelin down-regulates pro-inflammatory cytokines, including interleukin (IL)-1 beta and tumor necrosis factor (TNF)-alpha. Obestatin appears to decrease food intake and appetite, and its potential role in inflammation is not yet clear. The aims of this study were to assess total and acylated (active) ghrelin and obestatin serum levels and their relations with inflammatory status in rheumatoid arthritis (RA) patients. Design: Fasting blood samples were obtained from 37 patients with RA, 29 patients with Behcet's disease (BD) and 28 healthy controls (HC). Total ghrelin and obestatin levels were measured by radioimmunoassay and acylated ghrelin was quantified by enzyme-linked immunosorbent assay. Results: Patients with RA had lower total ghrelin, but higher obestatin levels than patients with BD (p < 0.05 for both), but when compared with HC group differences were not significant. There was no difference across groups in terms of acylated ghrelin. Total ghrelin level was not correlated with any study parameters in the all groups. Obestatin level correlated with erythrocyte sedimentation rate and DAS-28 in the RA group, the level of IL-6 in the BD group, and with the level of TNF-alpha in the HC group (r = 0.400, p < 0.05; r = 0.412, p < 0.05, r = 0.543, p < 0.01 and r = 0.528, p < 0.05, respectively). Conclusions: Our results did not show a significant correlation between circulating ghrelin and clinical or laboratory markers of disease activity in RA. Surprisingly, obestatin correlated with some inflammatory markers. So, obestatin seems to be more valuable than ghrelin in the pathogenesis of RA.
Keywords: ghrelin; obestatin; rheumatoid arthritis; Behcet's disease